Strategi Komunikasi Wartawan Kriminal Luwuk Post Dalam Mencari Berita Dimasa Pandemi Covid-19 - Alalik Nur Afifillah; Falimu (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The purpose of the study was to find out how the Luwuk Post Criminal Journalists Communication Strategies in Searching for News Amid the Covid-19 Pandemic. Being a journalist does not always have to wait until an event occurs, but with a sharp instinct a journalist will seek and observe. A journalist must be able to develop a communication strategy before carrying out his duties. To make it easier for journalists to dig up information or get data, choosing a strategy is the most appropriate step, therefore a journalist must be careful in planning their communication. Collecting data using observation (observations), questionnaires, and documentation. The population in this study are all criminal journalists in the Luwuk Post office. The results showed that the Communication Strategy used by the Luwuk Post Criminal Journalists in Searching for News during the Pandemic showed that they were very good at finding criminal news during the pandemic.